INNOVATION AND TECHNOLOGY IN IMPORTED CAR DETAILING: STRATEGIES FOR ENTREPRENEURIAL DIFFERENTIATION - Luz, Romário Junior dos Santos (LUMEN ET VIRTUS, 2023)
The automotive detailing industry, particularly in the luxury and imported vehicle segment, is experiencing a technological renaissance driven by innovation, sustainability, and customer-centric service models. Key developments include the use of nanotechnology-based coatings, Internet of Things (IoT) tools, and waterless cleaning products, all of which enhance vehicle protection while reducing environmental impact. Moreover, mobile service platforms, augmented reality (AR) training, artificial intelligence (AI)-powered diagnostics, and specialized customer relationship management (CRM) software are enabling unprecedented levels of personalization, efficiency, and operational excellence. This paper explores how these technologies empower entrepreneurs to differentiate their businesses in a competitive market, align with eco-conscious consumer expectations, and deliver premium service quality demanded by high-end client.